2016
DOI: 10.1016/j.celrep.2016.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Mdm2 Phosphorylation Regulates Its Stability and Has Contrasting Effects on Oncogene and Radiation-Induced Tumorigenesis

Abstract: SUMMARY ATM phosphorylation of Mdm2-S394 is required for robust p53 stabilization and activation in DNA damaged cells. We have now utilized Mdm2S394A knock-in mice to determine that phosphorylation of Mdm2-S394 regulates p53 activity and the DNA damage response in lymphatic tissues in vivo by modulating Mdm2 stability. Mdm2-S394 phosphorylation delays lymphomagenesis in Eμ-myc transgenic mice, and preventing Mdm2-S394 phosphorylation obviates the need for p53 mutation in Myc-driven tumorigenesis. However, irra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 69 publications
1
30
1
Order By: Relevance
“…Intriguingly, while Mdm2-S394 phosphorylation delays lymphomagenesis in E μ- myc transgenic mice, and preventing Mdm2-S394 phosphorylation obviates the need for p53 mutation in Myc-driven tumorigenesis, irradiated Mdm2 S394A mice display increased hematopoietic stem and progenitor cell functions, and decreased radiation-induced lymphomagenesis. These findings document contrasting effects of ATM-Mdm2 signaling on p53 tumor suppression (184). …”
Section: Phosphorylation Of Mdm Proteins By Atmmentioning
confidence: 87%
See 2 more Smart Citations
“…Intriguingly, while Mdm2-S394 phosphorylation delays lymphomagenesis in E μ- myc transgenic mice, and preventing Mdm2-S394 phosphorylation obviates the need for p53 mutation in Myc-driven tumorigenesis, irradiated Mdm2 S394A mice display increased hematopoietic stem and progenitor cell functions, and decreased radiation-induced lymphomagenesis. These findings document contrasting effects of ATM-Mdm2 signaling on p53 tumor suppression (184). …”
Section: Phosphorylation Of Mdm Proteins By Atmmentioning
confidence: 87%
“…Therefore, ATM phosphorylation of the negative regulator of p53, Mdm2, can profoundly impact p53 stabilization and activation in response to stress in vivo . In a subsequent study using Mdm2 S394A mice we showed that phosphorylation of Mdm2-S394 regulates p53 activity and the DNA damage response in lymphatic tissues in vivo by modulating Mdm2 stability (184). Intriguingly, while Mdm2-S394 phosphorylation delays lymphomagenesis in E μ- myc transgenic mice, and preventing Mdm2-S394 phosphorylation obviates the need for p53 mutation in Myc-driven tumorigenesis, irradiated Mdm2 S394A mice display increased hematopoietic stem and progenitor cell functions, and decreased radiation-induced lymphomagenesis.…”
Section: Phosphorylation Of Mdm Proteins By Atmmentioning
confidence: 99%
See 1 more Smart Citation
“…Since a minimum Mdm2 level is necessary for proper DNA replication, events that lower the amounts of intracellular Mdm2 might confer replication stress. For instance, Mdm2 levels drop in response to DNA damage, through phosphorylation and subsequent autoubiquitination of Mdm2 (45,46). This suggests that impaired DNA replication might occur in response to DNA damage, not only as a direct result of DNA lesions, but also as a consequence of Mdm2 degradation.…”
Section: Discussionmentioning
confidence: 99%
“…To understand the role of p53-TIGAR-mediated glycolytic suppression in FA HSCs, we first determined p53 activation in Fanca −/− HSPCs. We observed increased phosphorylation of p53 at Serine 18 (p53 Ser18 ), an established marker for p53 activation [38,39], in Fanca −/− BM LSK cells compared with WT cells (Fig. 3A).…”
Section: P53-tigar Attenuates Ros Dna Damage and Chromosomal Instabmentioning
confidence: 96%